Elongation at Midcell in Preparation of Cell Division Requires FtsZ, but Not MreB nor PBP2 in Caulobacter crescentus - van Teeseling, Muriel C. F. (Frontiers in Microbiology, 2021)
Controlled growth of the cell wall is a key prerequisite for bacterial cell division. The existing view of the canonical rod-shaped bacterial cell dictates that newborn cells first elongate throughout their side walls using the elongasome protein complex, and subsequently use the divisome to coordinate constriction of the dividing daughter cells. Interestingly, another growth phase has been observed in between elongasome-mediated elongation and constriction, during which the cell elongates from the midcell outwards. This growth phase, that has been observed in E. coli and C. crescentus, remains severely understudied and its mechanisms remain elusive. One pressing open question is which role the elongasome key-component MreB plays in this respect. This study quantitatively investigates this growth phase in C. crescentus and focuses on the role of both divisome and elongasome components. This growth phase is found to initiate well after MreB localizes at midcell, although it doesn’t require its presence at this subcellular location nor the action of key elongasome components. Instead, the divisome component FtsZ seems to be required for elongation at midcell. This study thus shines more light on this growth phase in an important model organism and paves the road to more in-depth studies.